2018
DOI: 10.1037/ccp0000315
|View full text |Cite
|
Sign up to set email alerts
|

Measuring fear change within exposures: Functionally-defined habituation predicts outcome in three randomized controlled trials for pediatric OCD.

Abstract: Habituation is conceptually consistent with multiple mechanistic theories and should continue to be investigated as a practical marker of initial extinction learning and possible moderator of the relationship between fear activation and outcome. Results support the importance of functional and frequent fear measurement during exposures, and discussion considers implications of these findings for future studies aiming to understand learning during exposure and improve exposure delivery. (PsycINFO Database Record Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 38 publications
1
45
0
Order By: Relevance
“…There is evidence from two studies that greater variability of distress during exposure is associated with better outcomes (Kircanski and Waters et al 2015). At post-treatment, Waters et al (2015) found a significant association between greater emotional variability and improved mixed anxiety severity immediately post-treatment, with a large effect size, although this association was not found by Benito et al (2018) or Kircanski and Peris (2015). However, at 3-month follow-up, Kircanski and Peris (2015) did find that greater emotional variability in distress was significantly associated with reductions in OCD severity, with a medium effect size.…”
Section: Variability Of Distressmentioning
confidence: 97%
See 3 more Smart Citations
“…There is evidence from two studies that greater variability of distress during exposure is associated with better outcomes (Kircanski and Waters et al 2015). At post-treatment, Waters et al (2015) found a significant association between greater emotional variability and improved mixed anxiety severity immediately post-treatment, with a large effect size, although this association was not found by Benito et al (2018) or Kircanski and Peris (2015). However, at 3-month follow-up, Kircanski and Peris (2015) did find that greater emotional variability in distress was significantly associated with reductions in OCD severity, with a medium effect size.…”
Section: Variability Of Distressmentioning
confidence: 97%
“…Five studies investigated the relationship between child distress during exposure and treatment outcomes (Benito et al 2018;Hedtke et al 2009;Kircanski and Peris 2015;Peterman et al 2016;Waters et al 2015).…”
Section: Distressmentioning
confidence: 99%
See 2 more Smart Citations
“…CBT+NIBS trials should also incorporate established treatment fidelity methods to ensure that the CBT is delivered, received, and enacted as intended (38,39). Quantification of process elements [e.g., patient/therapist behaviors (40)] and measurement of relevant moderators and mediators should also be considered, as these methods may reveal causes of variable outcomes, information that can in turn be used to further refine, personalize, or optimize the intervention.…”
Section: Consideration 4: Cbt Efficacy Varies Across Individuals and Practitionersmentioning
confidence: 99%